Is There a Rural Penalty in Language Acquisition? Evidence From Germany's Refugee Allocation Policy - Khalil, Samir; Kohler, Ulrich; Tjaden, Jasper (Frontiers in Sociology, 2022)
Emerging evidence has highlighted the important role of local contexts on integration trajectories of asylum seekers and refugees. Germany’s policy of randomly allocating asylum seekers across Germany may advantage some and disadvantage others in terms of opportunities for equal participation in society. This study explores the question whether asylum seekers that have been allocated to rural areas experience disadvantages in terms of language acquisition compared to those allocated to urban areas. We derive testable assumptions using a Directed Acyclic Graph (DAG) which are then tested using large-N survey data (IAB-BAMF-SOEP refugee survey). We find that living in a rural area has no negative total effect on language skills. Further the findings suggest that the ‘null effect’ is the result of two processes which offset each other: while asylum seekers in rural areas have slightly lower access for formal, federally organized language courses, they have more regular exposure to German speakers.